2016
DOI: 10.4236/oalib.1102791
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Stress of Children with Autistic Disorder

Abstract: Parents of children with autistic disorder experience a unique form of stress that varies significantly according to socio-cultural contexts. This review aims to investigate the stress levels of parents with children with autistic disorder and identify variables that predict parenting stress. A search of CINAHL, Springer, Pub Med, and EBSCO databases between the years 2001-2015 was conducted using the following keywords: parent stress, impact stress on parent, child with autistic disorder, psychological well-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 59 publications
(63 reference statements)
0
7
0
2
Order By: Relevance
“…In the second step, depressive symptoms in parents of children with ASD were predicted by employment and household income. This relationship between low socio-economic status and depression has been supported by numerous studies [18,19,29]. The adverse effects of economic hardship on both mental and physical health and functioning are evident from a young age and persist across a person's lifespan.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In the second step, depressive symptoms in parents of children with ASD were predicted by employment and household income. This relationship between low socio-economic status and depression has been supported by numerous studies [18,19,29]. The adverse effects of economic hardship on both mental and physical health and functioning are evident from a young age and persist across a person's lifespan.…”
Section: Discussionmentioning
confidence: 79%
“…Depressive symptoms in parents who do not have a job or have a lower household income were higher than for parents who have a job and higher income. Socio-economic support was indicated as being the primary predictor of mental health problems and mediated the relationship between child-related factors and parental psychological distress [18,22]. Taking care of children with ASD in daily life is a long journey; therefore, we should consider that the response of parents may vary in accordance with the process of children's growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The American Psychiatric Association's (APA, 2000) Diagnostic and StatisticalManual of Mental Disorders, Fourth Edition, Text Revision (DSM-IV-TR), defines ASD as a group of disorders that include autistic disorder, pervasive developmental disorder not otherwise specified (PDD-NOS), and Asperger's Disorder. The core deficits associated with an ASD are impairment in social interaction and communication, as well as the presence of unusual behaviors and/or interests (Al-Oran & Al-Sagarat, 2016). The symptoms and characteristics can manifest themselves in a wide variety of combinations from mild to severe.…”
Section: Family With Autism Childmentioning
confidence: 99%
“…Previous studies of children with ASD tend to involve a wide age range (e.g., 4–11 years) ( 12 ), which may mask the heterogeneity of the disorder. Furthermore, it has been reported that mothers of children under the age of 6 years experienced more challenges than those of school-aged children ( 26 ). To fill the abovementioned research gaps, this study investigated parenting stress in mothers of children with ASD between 2 and 6 years old.…”
Section: Introductionmentioning
confidence: 99%